Phonemic Error Analysis of a Tajikistan Student in Indonesian as a Foreign Language (BIPA) Learning at UIN Bandung - Azizir Rohma Febriyani; Yeti Heryati; Bustomi Bustomi (MASI Mandiri Edukasi, 2026)
Phonemic accuracy is a crucial aspect of Indonesian as a Foreign Language (BIPA) learning, yet foreign learners often experience persistent phonemic errors due to differences between their first language and Indonesian phonological systems. This study addresses the problem of phonemic errors produced by a Tajik student during BIPA learning, which may hinder intelligibility and effective communication. The objective of this research is to identify and analyze the types of phonemic errors and their phonological characteristics as manifested in the learner’s spoken Indonesian. This study employs an applied qualitative case study approach focusing on a single Tajik learner enrolled in a BIPA program at UIN Bandung. Data were collected through classroom observation, teaching participation, interviews, and voice-note recordings via WhatsApp, which provided authentic speech data. The data were analyzed using phonemic and phonological analysis to identify systematic error patterns. The results reveal recurring phonemic errors, particularly vowel mispronunciation involving the phoneme /e/ and consonant epenthesis after velar nasals, such as /ŋg/. These errors indicate strong first-language phonological influence and incomplete phonemic acquisition in Indonesian. The findings highlight the importance of targeted phonological instruction in BIPA learning.